Validity of Lectora Inspire-Based Interactive Learning Media Integrated with Camtasia Studio - Fathoni, Ahmad; Puspasari, Durinda (Journal of Office Administration : Education and Practice, 2023)
This study aims to analyze the process of developing interactive learning media based on Lectora Inspire, which is integrated with Camtasia Studio, for archiving subjects at SMKN 3 Bojonegoro. It also aims to assess the feasibility of the developed interactive learning media and examine student responses to it. The study utilizes the ADDIE R&D model, excluding the Evaluation stage, and employs both quantitative and qualitative data analysis techniques. The participants in the study were 20 students from class X OTKP 1. The developed products were subjected to validation by material experts and media experts. The validation results indicate a material expert validation rate of 86.25% for Expert 1 and 82.5% for Expert 2, while the media expert validation rates were 84.28% and 88.57% for Expert 1 and 2, respectively. The average validation score from the four validators was 85.4%, indicating a high level of feasibility. The student responses revealed an average score of 84%, indicating a high level of interest. Therefore, it can be concluded that the interactive learning media based on Lectora Inspire, integrated with Camtasia Studio, can effectively support archiving learning